Rancang Bangun Website Daur Hidup Batik Menggunakan Metode Waterfall Dan Kerangka Kerja Laravel - Aria Maulana Eka Mahendra; Galih Wasis Wicaksono; Agus Eko Minarno (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2024)
Batik is a traditional art that holds great value in human life. Through a creative process that involves the selection and application of unique motifs on fabric, batik produces alluring works of art. The use of batik is not limited to special moments, but has also penetrated into the world of modern fashion. The lifecycle of batik reflects a rich cultural heritage, boundless creativity and strong human identity. This makes batik a beautiful embodiment of human life, uniqueness, and diversity in maintaining and honoring cultural traditions. The purpose of this research is to create a web-based information platform about the life cycle of batik and provide access to data managers. This system has been built using the PHP programming language, supported by the MySQL database, and using the Laravel framework. The method applied in the development of this research is the waterfall approach. The results of this study produced a web-based information platform about the batik life cycle. Through black-box testing using Selenium Web Driver, this system was proven to operate properly. Thus, it can be concluded that this system meets the needs and is acceptable to users.